Dust - Cornwell, Patricia Daniels, 1953- (Sphere, 2013)
The twenty-first book in the Kay Scarpetta series, from No. 1 bestselling author Patricia Cornwell. 'America's most chilling writer of crime fiction' The Times After working on one of the worst mass killings in US history, Chief Medical Examiner Kay Scarpetta returns home to recover, but an unsettling call drives her straight back to work. The body of a young woman has been discovered inside the sheltered gates of MIT, draped in an unusual cloth and posed in a way that is too deliberate to be the killer's first strike. A preliminary examination reveals that the body is covered in a fine dust that under ultra-violet light fluoresces blood-red, emerald-green and sapphire-blue, and physical evidence links this to another series of disturbing homicides in Washington, DC. As she pieces together the fragments of evidence, Scarpetta discovers that the cases connect, yet also seem to conflict, drawing herself and her team deeper into the dark world of designer drugs, drone technology, organised crime, and shocking corruption at the highest level. Dust is a thrilling, addictive novel featuring one of the most iconic, original and compelling characters in crime fiction today.